PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN METODE PENEMUAN UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS XI MIA 3 SMA NEGERI 4 KUNDUR - Maisaroh, Siti; Murni, Atma; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research to improve the learning process and the students mathematical understanding skill by implementation cooperative learning model with the discovery method. The type of this research is classroom action research with two cycles. This research was conducted at class XI MIA 3 SMA Negeri 4 Kundur of the first semester to 24 students on 2019/2020 academic year on matrix material. The research instruments used mathematical learning instruments (syllabus, lesson plans, and student worksheets) and instruments for collecting data (observation sheets and mathematical understanding tests). Qualitative data were collected by observation technique with observation sheets which aimed to obtain data on the activities of teacher and students. Quantitative data was collected by a test technique using a mathematical understanding ability test kit that aimed to collected students mathematical understanding ability data. Base on the analysis of the observation sheets showed that the quality of implementation of learning process was improved at each meeting. Students have been more active in learning and their participation in increasing knowledge is also getting better. Result of the test indicated that the student’s learning achievement for the first was 48,14 improved in 1st cycle to 60,87 and improved to be 79,73 in 2nd cycle. Students qualification also improved for the 2nd cycle high qualification was 66,7%, medium qualification was 8,3% and low qualification was 25% when compared to 1st cycle that was high qualification was 33,3%, medium qualification was 33,3% and low qualification was 33,3% while the first high qualification was 25%, medium qualification was 12,5% and low qualification was 62,5%Key Words: Cooperative Learning, Discovery Method, Mathematical Understanding Skill